Work Environment as a Moderating Variable of the Influence of Work Ethic on Employee Performance - Widya Lusi Arisona; Ifadhila; Muh Amrih; Ade Sarengat Pakanheran; Raihan A. Hanasi (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This research is a quantitative study with an explanatory approach, an approach that makes previous studies the main foundation for proving hypotheses at a higher stage, namely the proof stage. The data obtained by the researcher came from two hundred and ninety-five employees of Bank Mega Syari'ah spread throughout Indonesia  The data obtained by the researcher was analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the first hypothesis in this study, namely that the Work Ethics variable can have a positive relationship direction and a significant influence on Employee Performance and the Work Environment variable can strengthen the influence of the Work Ethics variable on Employee Performance. Based on the results of the third table above, the first hypothesis in this study can be accepted because the P-Values are positive and below the 0.05 significance level, namely 0.028. These results indicate that a good Work Ethics can create good relationships with superiors, fellow coworkers, and can make it easier for employees to complete their work. In the next hypothesis, the results of the third table above also show that the Work Environment variable can moderate the influence of the Work Ethics variable on Employee Performance. Based on this, the first and second hypotheses in this article.